UPSHOT OF SERVICE AND PRICES ON LOYALTY THROUGH SATISFACTION AS INTERVENING VARIABLES (Case study in "PALAPA TOSERBA" SURABAYA) - Qomariyah, N; Kudsi As.ari, MH (JMM17 : Jurnal Ilmu ekonomi dan manajemen, 2022)
Abstract. This study is intended to determine the effect of service and price on customer satisfaction and their impact on customer loyalty at "Palapa Toserba" Surabaya. The population used in this study were all consumers in "Palapa Toserba" Surabaya. The sampling technique used is a non-probability sampling technique precisely accidental sampling , which is a sampling technique based on chance, that is, all members of the population who coincidentally meet with the researcher can be sampled in the study. The sample used in this study was 75 respondents. The test tool used is a path analysis technique with the help software SPSS 17.0From the results of the study concluded that: 1). Service has a direct and significant effect on customer loyalty at "Palapa Toserba" Surabaya, 2). Price has a direct and significant effect on customer loyalty at "Palapa Toserba" Surabaya, 3). Service has a direct and significant effect on customer satisfaction at "Palapa Toserba" Surabaya, 4). Price has a direct and significant effect on customer satisfaction at "Palapa Toserba" Surabaya, 5). Customer satisfaction has a direct and significant effect on customer loyalty at "Palapa Toserba" Surabaya, 6). Service has an indirect effect on customer loyalty through customer satisfaction at "Palapa Toserba" Surabaya, 7). Price has an indirect effect on customer loyalty through customer satisfaction at "Palapa Toserba" Surabaya